Tolerance to arsenic contaminant among multidrug-resistant and copper-tolerant Salmonella successful clones is associated with diverse ars operons and genetic contexts - Mourao, J (2020)
Emergence and expansion of frequent multidrug-resistant (MDR) major Salmonella clones/serotypes has been a significant threat in the last years. Metal compounds, such as copper, commonly used in animal-production settings, have been pointed out as possible contributors for the selection of such strains/clones. However, the scarcity of studies limits our understanding of the impact of other metal environmental contaminants as arsenic (used in insecticides/herbicides/coccidiostats). We analysed arsenic tolerance (AsT) dispersion by phenotypic and genotypic (PCR/sequencing/I-CeuI/S1/XbaI-PFGE/hybridization) assays among Salmonella with diverse epidemiological and genetic backgrounds. Then, to better understand ars operon genetic contexts, the whole genome of five representative strains was sequenced. We found a high dispersion of ars operons conferring AsT, especially among copper-tolerant and relevant serotypes/clones related to pig-production setting. The acr3-type was found dispersed in the chromosome of diverse serotypes, including the emergent S. Rissen. Conversely, arsBII was almost confined to the MDR ST34 European clone of S. Typhimurium/S. 4,[5],12:i:-, always along with copper/silver tolerance sil + pco clusters in an integrative conjugative element. These data suggest that AsT is an essential adaptive feature for the ecological success of these epidemic clones/serotypes and alerts for global strategies to reduce arsenic-based compounds' impact thus preventing environmental/food contamination with frequent MDR foodborne pathogens.